Peluang Investasi dan Pengembangan Energi Biomassa: Perspektif Pemanfaatan dan Daya Saing Pengembangannya - Fitriliana Fitriliana; Syaifuddin Yana; Maryam Maryam; Rahmi Rahmi; Rita Nengsih; Cut Rusmina; Sufitrayati Sufitrayati; Asnariza Asnariza (Fakultas Teknik, 2023)
The current achievement range for renewable energy is around 12%, making it the greatest hurdle. Investment in biomass renewable energy has positive environmental and social impacts despite its lucrative financial potential. However, there are a number of dangers associated with this investment. Therefore, investment might be successful in the development of sustainable and sustainable biomass energy if a thorough investigation and careful planning are carried out. Biomass energy has a lot of potential, but it has yet to reach its full potential because of challenges like high production costs, inconsistent biomass availability, and a lack of supporting infrastructure. Policy and regulatory support, research and innovation, management of the biomass supply chain, increased production scale, diversified biomass sources, increased awareness and education, public-private partnerships, increased efficiency, consolidation of support finance, and environmental impact management are all crucial steps toward a solution. Improvements in conversion technology, sustainable management of biomass resources, increased government assistance, and investments in supporting infrastructure are all necessary steps toward making Indonesia's biomass energy more competitive on the global stage.